A leap of faith into the common byways: performing arts as a tool for ‘sensory’, ‘affective’ and ‘performative’ criminology to explore the symbolic and emotional worlds of violent crime - Turhal, Özlem (Criminological encounters, 2023)
Researchers delving into the socio-criminological field and attentively exploring the most inno- vative methodologies acknowledge that, in conjunction with research methods relying on oral and writ- ten language, a new range of non-textual strategies has emerged as an alternative mode of knowledge ac- quisition. This essay proposes an exploratory approach to gather the practices of theatre and criminology together in investigating and understanding violent crime and criminals through performing arts with a sensory methodology that takes imaginative and bodily encounters as a crucial part of knowledge pro- duction. The intention is to try to establish a medium where criminologists and theatre artists mutually contribute to a platform to scrutinize crime through their ‘arts’. In this work, we suggest that exploring, experiencing and staging the phenomena of crime with the actor’s body and their art as a channel can inspire and add layers to criminology studies and teaching.